PENGEMBANGAN PROFESIONALISME GURU DALAM MEMANFAATKAN GOOGLE CLASSROOM SEBAGAI MEDIA PEMBELAJARAN - abdul haris hasmar; Amiruddin (Al-Fikrah, 2021)
The purpose of this research is to provide ideas or ideas for stakeholders in developing teacher competence to use google classroom as a medium of learning in this digital era. In addition, it is also to provide an overview of the impact of developing teacher professionalism in utilizing google classroom media as a learning medium. The type of research is descriptive qualitative, that is the research that explain the data narratively appropriate to the result of research that researcher gets. The results show that the role of stakeholders in developing teacher competence to utilize google classrooms as a learning medium in this digital era is very large, including teachers can be skilled in using google classrooms, teachers can produce fun learning activities, can improve student learning outcomes and can improve performance. teachers in the digital era so that the professional competence of teachers can always be updated in mastering technology and information.